Complication Differences Between the Tumescent and Non-Tumescent Dissection Techniques for Mastectomy: A Meta-Analysis - Yang, Yi; Zhu, Juanying; Qian, Xinghua; Feng, Jingying; Sun, Fukun (Frontiers in Oncology, 2022)
Purpose: We conducted a systematic literature search and pooled data from studies to compare the incidence of complications between the tumescent and non-tumescent techniques for mastectomy. Methods: We searched PubMed, Embase, BioMed Central, Ovid, and CENTRAL databases for studies comparing the two mastectomy techniques up to November 1st, 2020. We used a random-effects model to calculate odds ratios (OR) with 95% confidence intervals (CI). Results: Nine studies were included with one randomized controlled trial (RCT). Meta-analysis indicated no statistically significant difference in the incidence of total skin necrosis (OR 1.18 95% CI 0.71, 1.98 I2=82% p=0.52), major skin necrosis (OR 1.58 95% CI 0.69, 3.62 I2=71% p=0.28), minor skin necrosis (OR 1.11 95% CI 0.43, 2.85 I2=72% p=0.83), hematoma (OR 1.19 95% CI 0.80, 1.79 I2=4% p=0.39), and infections (OR 0.87 95% CI 0.54, 1.40 I2=54% p=0.56) between tumescent and non-tumescent groups. Analysis of studies using immediate alloplastic reconstruction revealed no statistically significant difference in the incidence of explantation between the two groups (OR 0.78 95% CI 0.46, 1.34 I2=62% p=0.37). Multivariable-adjusted ORs on total skin necrosis were available from three studies. Pooled analysis indicated no statistically significant difference between tumescent and non-tumescent groups (OR 1.72 95% CI 0.72, 4.13 I2=87% p=0.23). Conclusion: Low-quality evidence derived mostly from non-randomized studies is indicative of no difference in the incidence of skin necrosis, hematoma, seroma, infection, and explantation between the tumescent and non-tumescent techniques of mastectomy. There is a need for high-quality RCTs to further strengthen the evidence.